2021
DOI: 10.5194/acp-2021-41
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercomparison of wind observations from ESA's satellite mission Aeolus, ERA5 reanalysis and radiosonde over China

Abstract: Abstract. The European Space Agency (ESA) Earth Explorer Atmospheric Dynamics Mission Aeolus is the first satellite mission providing wind profile information on a global scale, and its wind products have been released on 12 May 2020. In this study, we verify and intercompare the wind observations from ESA’s satellite mission Aeolus and the European Centre for Medium-Range Weather Forecasts (ECMWF) fifth generation atmospheric reanalyses (ERA5) with radiosonde (RS) observations over China, to allow a fitting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The main verification methods have included radiosonde (Baars et al, 2020) and airborne lidar (Lux et al, 2020;Witschas et al, 2020), in which Aeolus's prototype atmospheric laser Doppler instrument airborne demonstrator was used. Over the following 2 years, researchers worldwide completed regional verification of the Aeolus detection data using various detection methods, including satellites (Shin et al, 2020), groundbased lidar (Hauchecorne et al, 2020), ground-based wind profiler radar (Belova et al, 2021;Guo et al, 2021), and radiosonde (Liu et al, 2021). In addition, global Aeolus data verification studies using the numerical weather prediction (NWP) model have been undertaken (Rennie and Isaksen, 2019;Martin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The main verification methods have included radiosonde (Baars et al, 2020) and airborne lidar (Lux et al, 2020;Witschas et al, 2020), in which Aeolus's prototype atmospheric laser Doppler instrument airborne demonstrator was used. Over the following 2 years, researchers worldwide completed regional verification of the Aeolus detection data using various detection methods, including satellites (Shin et al, 2020), groundbased lidar (Hauchecorne et al, 2020), ground-based wind profiler radar (Belova et al, 2021;Guo et al, 2021), and radiosonde (Liu et al, 2021). In addition, global Aeolus data verification studies using the numerical weather prediction (NWP) model have been undertaken (Rennie and Isaksen, 2019;Martin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ERA5 launched by ECMWF is currently the most powerful global climate atmospheric reanalysis tool, which provides hourly data and uncertainty estimates of various atmospheric, land and ocean state parameters. Additionally, it has also been widely used for atmospheric parameter estimation [36][37][38]. Existing studies [36,[38][39][40] have shown the accuracy and applicability of wind speed and temperature in ERA5 data.…”
Section: Era5 Accuracy Analysismentioning
confidence: 99%
“…Additionally, it has also been widely used for atmospheric parameter estimation [36][37][38]. Existing studies [36,[38][39][40] have shown the accuracy and applicability of wind speed and temperature in ERA5 data. Hersbach H et al [41] as well showed the good performance of ERA5 data.…”
Section: Era5 Accuracy Analysismentioning
confidence: 99%
“…The availability of the Aeolus dataset provides the unique opportunity to directly assess the performance of AMVs derived from different retrieval channels relative to a global reference wind profile dataset observed by a single unit. Such a direct comparison has not previously been possible due to the sparse spatial coverage of other available reference datasets, e.g., rawinsonde winds (e.g., Chen et al, 2021;Liu, B. et al, 2021;Martin et al, 2021). Further, Aeolus observations are made at a set of fixed vertical levels that represent the averages of accumulated measurements within vertical range bins.…”
Section: Introductionmentioning
confidence: 99%